Analisis Teknik Entity-Relationship Diagram Dalam Perancangan Database - Pulungan, Syahidannur Mukminah; Febrianti, Reza; Lestari, Titin; Gurning, Natra; Fitriana, Nur (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
The purpose of this research is to find out how to develop the data entity relationship model in the data based data management system. Where the entity relationship is a system that is important for the company or as a liaison to explain the relationship between data and database systems. There are many techniques used in database design. One of them is Entity Relationship Diagram (ERD). ERD is one of the main diagrams representing the conceptual data model that reflects the user data requirements in the database system. ERD is the first stage in database design. There are several things that must be considered in making ERD for database design. Each database must have entities that are interconnected and each entity must have attributes consisting of a primary key as the entity's characteristics and descriptive attributes. Many users fail to create databases due to errors in ERD creation. Conceptual errors, procedural errors, or technical errors. This article was created using the SLR method, namely reviewing various kinds of references that discuss database design, then drawing conclusions to make it easier for users to overcome problems that occur when making ERD and implementing them.